Reduced Plasma Magnesium Levels in Type-1 Diabetes Associate with Prothrombotic Changes in Fibrin Clotting and Fibrinolysis - Sobczak, Amélie I. S.; Phoenix, Fladia A.; Pitt, Samantha J.; Ajjan, Ramzi A.; Stewart, Alan J. (Thrombosis and Haemostasis, 2020)
Individuals with type-1 diabetes mellitus (T1DM) have a higher risk of thrombosis and low plasma magnesium concentrations. As magnesium is a known regulator of fibrin network formation, we investigated potential associations between fibrin clot properties and plasma magnesium concentrations in 45 individuals with T1DM and 47 age- and sex-matched controls without diabetes. Fibrin clot characteristics were assessed using a validated turbidimetric assay and associations with plasma magnesium concentration were examined. Plasma concentrations of fibrinogen, plasminogen activator inhibitor-1 (PAI-1), and lipids were measured and fibrin fiber diameters assessed using scanning electron microscopy. Fibrin clot maximum absorbance was unchanged in subjects with T1DM compared with controls, while lysis time was prolonged (p = 0.0273). No differences in fibrin fiber diameters or in lipid profile were observed between T1DM and controls. PAI-1 concentration was lower in the T1DM group compared with the controls (p = 0.0232) and positively correlated with lysis time (p = 0.0023). Plasma magnesium concentration was lower in the T1DM group compared with controls (p < 0.0001). Magnesium concentration negatively correlated with clot maximum absorbance (p = 0.0215) and lysis time (p = 0.0464). A turbidimetric fibrin clot lysis assay performed in a purified system that included PAI-1 and 0 to 3.2 mM Mg2+ showed a shortening of lysis time with increasing Mg2+ concentrations (p = 0.0004). Our findings reveal that plasma magnesium concentration is associated with changes in fibrin clot and lysis parameters.
Keywords: clot lysis; coagulation; metal homeostasis; plasminogen activator inhibitor-1; thrombosis